Handbook of research on hybrid learning models [ advanced tools, technologies, and applications - Fong, Joseph; Kwan, Reggie; Wang, Fu Lee (Gale virtual reference library, 2010)
"This book focuses on Hybrid Learning as a way to compensate for the shortcomings of traditional face-to-face teaching, distance learning, and technology-mediated learning"--Provided by publisher.